Review of Compensation and Work Stress on Employee Performance in The Medical Records Department at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta - Putra, Adittia Ammanda; Azis, Abdul (International Journal of Social Sciences, 2025)
The purpose of this study was to determine the effect of compensation and organizational work stress on employee performance in Medical Records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta, both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used is saturated sampling technique, namely using a sample of 80 respondents from the entire population. Data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, coefficient of determination analysis, hypothesis testing. This is evidenced by the results of the compensation hypothesis test obtained a t-value of 4,611> t-table 1,990 and strengthened by the ρ value <Sig.0.05 or significance value <0.05 (0.000 <0.05) work stress obtained a t-value of 6,152> t-table 1,990 and strengthened by the ρ value <Sig.0.05 or significance value <0.05 (0.000 <0.05). The results of the study of compensation and work stress simultaneously have a significant effect on employee performance in Medical Records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta, shown by the multiple linear regression equation Y = 9.054 + 0.314X1 + 0.476X2. This is proven by the results of the simultaneous hypothesis test obtained the F count value (74.569 > F table 3.12) and is strengthened by a significance value <0.00 (0.000 <0.05). The results of the coefficient of determination test of the compensation and work stress variables have an influence of 65.1% on employee performance in Medical Records at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta. Thus, H03 is accepted and H3 is rejected. This means that there is a proven insignificant influence simultaneously between compensation (X1) work stress (X2) employee performance (Y).